Geomorphosite assessment in Montesinho Natural Park (Portugal) - Pereira, Paulo (2007)
The Montesinho Natural Park (MNP), with an area of about 750 km2, is one of the largest protected areas in Portugal. Since its inauguration as a natural park in 1979, geological and geomorphological aspects have not been taken into consideration in its nature conservation policies. Over the last few years, this deficit has been compensated with an assessment of its geomorphological heritage. The assessment was made possible due to a research project on the geological heritage of the natural parks of north-eastern Portugal. The assessment method propagated herein proposes a clear definition of three types of geomorphosites: single places, geomorphological areas or panoramic viewpoints. Further, it proposes as two-staged approach to assessment with inventory compilation followed by quantification of value. Inventory compilation, for example, involves the identification and qualitative assessment of potential geomorphosites and, therefore, the selection and characterization of geomorphosites. The quantification stage includes the numerical assessment of sites and their final ranking. The values are numerically assessed using selected criteria. The implementation of this approach in the MNP led to the identification of 154 potential geomorphosites, of which only 26 were selected after the qualitative assessment or characterisation process. The numerical assessment of the sites and their ranking allowed a final selection of 13 sites for public use.